Beyond Structural Writing Instruction: A Multisite Study of Epistemic and AI Governance Needs in Indonesian Language Teacher Education - Faradilla Intan Sari; Vismaia S. Damayanti; Andoyo Sastromiharjo (Journal of Education Research, 2026)
Scientific article writing demands evidence investigation, source synthesis, representational transformation, argumentation, and responsible AI regulation—extending beyond textual structure mastery. This study examined the mismatch among students' initial writing capability, instructional processes, representational practices, AI use, and instructional development priorities. A multisource descriptive design was employed during the analysis and exploration phase of Educational Design Research, involving 120 seventh-semester students and six lecturers from Indonesian Language Education programs at three universities in West Java. Data were collected through article assessments, questionnaires, classroom observations, interviews, and document analysis, then analyzed using descriptive statistics, needs indices, and thematic procedures. The mean initial writing score was 61.50, with 71.67% of students rated fair or below. Argumentation was the weakest dimension (2.59), and representational competence averaged 47.67 out of 100. Although 88.33% of students had used AI, verification and disclosure practices remained underdeveloped. The student needs index reached 89.47 and the lecturer needs index 94.44. Findings identify AI governance, argument mapping, literature synthesis, and formative feedback as primary development priorities.